FRAMEWORK FOR ASSESSMENT OF PRODUCT QUALITY. THE QUALITY OF PRODUCTS, THEIR CLASSIFICATION AND EVALUATION METHODS - Martynenko, S. V.; Poliakov, V. P. (Science and Transport Progress, 2006)
The quality indicators of functioning of the quality management system and assessment methods of indicators of product quality are presented.